Biological dan Molecular Characterization of Papaya Ringspot Virus from Bogor District, Indonesia - Riska, Riska; Husada, Eko Darma; Budiyanti, Tri; Jumjunidang, Jumjunidang (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2023)
Management of PRSV using cross-protection and transgenic plants has been hampered due to varying PRSV gene sequences. Therefore, the characterization of new PRSV isolates could help design the region needed for region-specific management practices. The study aimed to characterize the typical PRSV isolates found in Bogor biologically and molecularly. The study was conducted in 2 stages: host range study of 2 isolates (Sukaraja and Cijeruk) on five species with six plants for replication, and RT-PCR analysis amplified coat protein (CP) region using PRSV326 and PRSV800 primer pair. The results showed that Sukaraja isolate produced systemic symptoms in papaya (Carica papaya L) cv. Merah Delima in the form of leaf lamina becoming pale and wilting, leaf malformation, open veins, and striped patterns on the leaves, while the Cijeruk isolate causes symptoms of leaf blistering, mosaicism, leaf malformation, wilted lamina, and striped patterns on the leaves. These two isolates did not cause symptoms on eggplant (Solanum melongena) and chickpea (Vigna unguiculata) but produced striped leaf patterns and pale lamina symptoms on bitter melon (Momordica charantia) and melon (Cucumis melo) leaves. RT-PCR analysis was able to amplify ±475 bp of DNA. The two DNA isolates had a homology percentage of 97.7% with PRSV isolates from Thailand, ranging between 93.07-99.68% with the Kulon Progo and Nganjuk isolates. Based on phylogenetic analysis, the Cijeruk isolate was in the same branch as the Indonesian isolate, while the Sukaraja isolate was a separate branch and closely related to isolates from Oklahoma and Malaysia.